Interactive effects of tree species composition and water availability on growth and direct and indirect defences in Quercus ilex. Issue 5 (24th March 2022) - Galmán, Andrea; Vázquez‐González, Carla; Röder, Gregory; Castagneyrol, Bastien
Abstract : Plant diversity has often been reported to decrease insect herbivory in plants. Of the numerous mechanisms that have been proposed to explain this phenomenon, how plant diversity influences plant defences via effects on growth has received little attention. In addition, plant diversity effects may be contingent on abiotic conditions (e.g. resource and water availability). Here, we used a long‐term experiment to explore the interactive effects of tree species composition and water availability on growth, direct (i.e. phenolics) and indirect (i.e. volatile organic compounds – VOCs) defences and leaf herbivory in Quercus ilex . We quantified herbivory by chewing insects, phenolic compounds and VOCs in Q. ilex trees growing in stands differing in tree species composition ( Q. ilex, Q. ilex + Betula Pendula, Q. ilex + Pinus pinaster and Q. ilex + B. pendula + P. pinaster ) and water availability (irrigated versus control). Both direct and indirect defences were affected by tree species composition, but such changes were not mediated by changes in tree stem diameter. Quercus ilex trees growing in stands with P. pinaster had the lowest concentration of both direct and indirect defences. Importantly, the effects of tree species composition on VOCs were exacerbated on irrigated blocks. Despite variation in defences, tree species composition did not affect herbivory in Q. ilex . Accordingly, we did not find any association between defences and insect herbivory. Our results suggest that changes in the micro‐environment rather than growth‐defence associations may mediate tree diversity effects on defences. In addition, reduced defensive investment in more diverse stands could negatively impact tree resistance masking the beneficial effects of species diversity at reducing insect herbivory.